Direct UV-MALDI-TOF MS analysis of (Glyco)proteins of fractions of bovine seminal plasma - Cerezo, A.S. (2007)
Bovine seminal plasma was submitted to chromatography on Con A-Sepharose. The "noninteracting", "weakly-interacting" and "strongly-interacting" fractions were analyzed through UV-MALDI-TOF MS together with a subfraction of the "non-interacting" material, using sinapinic acid (SA) as matrix. The spectra were obtained in linear positive mode in the 4.0-90.0 kDa mass/charge range showing peaks in well defined zones, namely: 5.5-8.0 kDa, 10.0-12.0 kDa, 12.5-14.0 kDa (major), 23.2-23.7 kDa, 26.1-27.5 kDa and 38.0-40.0 kDa. High sensitivity spectra showed some very small peaks until 90 kDa. Bovine seminal protein (BSP-A3), acidic seminal fluid protein (aSFP) and PDC-109 glycoproteins (BSP-A1 and BSP-A2) were identified. Caltrin, the human epididymis-specific glycoprotein (HE4), the calcium transport inhibitor protein, the inhibitor of metalloprotease 2 (TIMP-2), osteopontin (OPN) and the prostatic acid protease (PAP) were tentatively identified. The molecular weight of some peaks can be arranged in a sequence from that of BSP-A3 going through the molecular weights of glycoforms (including the known BSP-A1 and BSP-A2) which differ in the amounts of neutral hexoses and sialic acids, composing a BSP-family more extended than previously reported. Another two families could be builded up from proteins of molecular weight of about 12730 and 12750 Da and glycoforms which differ from them also by hexoses and sialic acids. The structures of the deduced O-linked oligosaccharides of the glycoforms are in complete agreement to that determined for the BSP-A1 Oligosaccharide. Small differences in the m. w. of some (glyco)proteins were attributed to genetic polymorphysm. The identification of proteins and O-linked glycoproteins in the "interacting" fractions of the chromatography suggests that the fractionation was not due to specific affinity interactions but to non-specific hydrophobic interactions of the proteins with the hydrophobic pocked of the Con A.